Internal Hernia Through Foramen of Winslow a Rare Cause of Small Bowel Obstruction: A Case Report - Nair, Vipin Venugopal; Parmjit, Malik; Sharma, Pawan; Raja, Sarali Santhosh; Aprajita, Atreya (Lietuvos chirurgija, 2023)
Internal hernia through foramen of Winslow (FoW) is rare condition as there are only 200 cases reported so far in the literature. Our patient a 78 years man presented with a clinical picture suggestive of small bowel obstruction for 5 days. Patient underwent emergency laparotomy following suspicion of internal hernia on imaging. On exploratory laparotomy there was grossly dilated bowel loops and a small segment of terminal ileum and omentum was found herniating through FoW in to the lesser sac. The bowel segment was reduced with gentle traction and herniated segment of omentum was excised due to questionable viability. Opening of FoW was unusually large and to prevent hernia recurrence it was closed partially. Postoperative period was uneventful. This unusual case presented to us diagnostic confusion and management challenge considering the previous history, multiple comorbidities and geriatric profile.